2007
DOI: 10.1111/j.1463-1318.2007.01343.x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative intraperitoneal adhesion pathophysiology

Abstract: Aside from the normal 'ad integrum' peritoneal regeneration, the postoperative intraperitoneal adhesion formation process may be considered as the pathological part of peritoneal healing following any injury, particularly a surgical one. Despite a large body of clinical and experimental studies, its pathophysiology remains controversial. Moreover, a better understanding of the pathophysiological events and of the medical and surgical factors involved in the adhesion formation process is pivotal in any attempt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
73
0
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 110 publications
1
73
0
7
Order By: Relevance
“…It involves a cascade of cellular, biochemical and immunological factors. [25] Inflammatory cellular activity in mesothelial regeneration and the alteration of the peritoneal fibrinolytic system are considered as the main pathways of adhesion formation. [25] According to our findings, MB application reduces adhesion formation after peritonitis based on alterations determined in adhesion scores, whereas it impairs wound healing as depicted by reduction in serum TNF-α and tissue 5-HP levels.…”
Section: Discussionmentioning
confidence: 99%
“…It involves a cascade of cellular, biochemical and immunological factors. [25] Inflammatory cellular activity in mesothelial regeneration and the alteration of the peritoneal fibrinolytic system are considered as the main pathways of adhesion formation. [25] According to our findings, MB application reduces adhesion formation after peritonitis based on alterations determined in adhesion scores, whereas it impairs wound healing as depicted by reduction in serum TNF-α and tissue 5-HP levels.…”
Section: Discussionmentioning
confidence: 99%
“…Both the peritoneal injury and the presence of foreign material enhance adhesion formation: these factors induce increased vascular permeability followed by an inflammatory response with a simultaneous release of inflammatory proteins (Zinther et al 2010). Several investigations have revealed that surgery leads to ingrowths of fibroblasts into the fibrin matrix, depositing collagen and resulting in the formation of connective tissue and adhesion (fibrous bands) between the injured peritoneal surfaces (Holmdahl 1997;Duron 2007). As the aim of our study was to investigate the feasibility of laparoscopic abomasal cannulation, which would be an important research tool in animal nutrition research, and most such research ends before removal of the cannula, we did not investigate the time of persistence of the adhesions afterwards.…”
Section: Discussionmentioning
confidence: 99%
“…Aproximadamente 60 ml de líquido peritoneal son producidos por hora, pero la cavidad peritoneal normalmente contiene sólo una pequeña cantidad de este líquido (Browning 2005). El líquido peritoneal normalmente contiene muchas de las proteínas plasmáticas, dentro de las cuales el fibrinógeno interviene durante el proceso inflamatorio intraperitoneal, especialmente en el período intra y postoperatorio, en donde se forman las adherencias (Duron 2007). De acuerdo a Hanson y col (1992), el líquido peritoneal refleja el estado patofisiológico de las superficies mesoteliales parietales y viscerales, por lo cual manipulaciones adicionales del peritoneo asociadas a resección y anastomosis de dos segmentos de intestino tendrían pequeñas consecuencias comparado con el trauma inducido en una celiotomía exploratoria.…”
Section: Introductionunclassified
“…En mamíferos machos, forman un espacio cerrado, mientras que en hembras existe una potencial comunicación al exterior vía cuernos uterinos. El peritoneo parietal se encuentra inervado por ramas de nervios espinales y contiene nociceptores térmicos, químicos y mecánicos (Duron 2007), los cuales son capaces de procesar estímulos dolorosos agudos localizados (Hollinshead 1953, Browning 2005. El peritoneo visceral, en contraste, está inervado por aferentes simpatéticos y reacciona a estímulos producidos por distensión, estiramiento, isquemia e inflamación (Browning 2005).…”
Section: Introductionunclassified